KOMUNIKASI KEBIJAKAN DALAM PENGELOLAAN PENGADUAN PELAYANAN ADMINISTRASI KEPENDUDUKAN MELALUI SP4N-LAPOR DI KOTA BANJAR - Zihan Apriani; Teguh Anggoro; Tofan Ibrahim (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This study aims to analyze policy communication in managing complaints related to population administration services through the SP4N-LAPOR system at the Department of Population and Civil Registration of Banjar City. This research employs a qualitative approach. Data were collected through interviews, observations, and documentation with informants selected using purposive sampling techniques, namely the Head of the Department of Population and Civil Registration of Banjar City, the SP4N-LAPOR operator at the Department of Population and Civil Registration of Banjar City, the SP4N-LAPOR operator at the Department of Communication and Informatics of Banjar City, and members of the public who use the services. The analysis of this research uses the policy implementation theory of George C. Edwards III, which emphasizes the communication dimension consisting of information transmission, clarity of information, and consistency of information. The results show that policy communication in managing complaints through SP4N-LAPOR at the Department of Population and Civil Registration of Banjar City has been carried out through various communication media, such as government social media platforms used as a means of socialization to the public. Information regarding the complaint mechanism has been delivered to the public; however, public understanding of how to use the system is still uneven. Meanwhile, in terms of information consistency, every public report submitted through SP4N-LAPOR is followed up by the Department of Population and Civil Registration in accordance with the applicable procedures.In general, policy communication in managing complaints related to population administration services through SP4N-LAPOR in Banjar City has been implemented; however, strengthening efforts are still needed in the aspect of public outreach to improve public understanding of the use of the complaint system.